Milestones in Water Reuse - Lazarova, Valentina; Asano, Takashi (IWA Publishing, 2013)
Milestones in Water Reuse: The Best Success Stories illustrates the benefits of water reuse in integrated water resources management and its role for water cycle management, climate change adaptation and water in the cities of the future. Selected case studies are used to illustrate the different types of water reuse, i.e. agricultural irrigation, golf course and landscape irrigation, urban and industrial uses, environmental enhancement, as well as indirect and direct potable reuse. The various aspects related to water reuse are covered, including treatment technologies, water quality, economics, public acceptance, benefits, keys for success and main constraints. These international case studies highlight the best practices for the implementation of water reuse and provide the perspective for the integration of water recycling projects in the future, both for megacities and rural areas.Milestones in Water Reuse: The Best Success Stories demonstrates that planned water reuse is a cost competitive and energy-saving option to increase water availability and reliability. This book provides policy makers and regulators with a good understanding of water reuse and helps them to consider recycled water as safe and how it can be used. It is intended to be read by all people in the water sector and shows how water reuse is safe, economically viable, environmentally friendly and can provide high social benefits.